EAPEAT al Carnaval de Barranquilla: tras las huellas de los Diablos Arlequines de Sabanalarga (2023)
The present work is a systematization of the artistic-pedagogical experience to the current state of the tradition of the Carnival of Barranquilla 2023, which has as a focus of inquiry the artistic and historical particularities of the patrimonial dance of the Diablos Arlequines de Sabanalarga, this manifestation have been important in the development of a festival as the Carnival of Barranquilla and in the same way for the representation of this abroad